How Does the Central Nervous System for Posture and Locomotion Cope With Damage-Induced Neural Asymmetry? - Le Ray, Didier; Guayasamin, Mathias (Frontiers in Systems Neuroscience, 2022)
In most vertebrates, the biomechanical apparatus ensuring posture and locomotion is characterized by a symmetrical disposition of their effectors around the main body axis. Logically, basic postural and locomotor actions thus result from various commands organized by sensory-motor neural networks symmetrically arranged during CNS development. However, many developmental and/or life accidents may alter such organization and generate asymmetries in motor operation that are often at least partially compensated for. First, we briefly present the basic sensory-motor organization of posturo-locomotor networks in vertebrates. Next, we review some aspects of the neural plasticity that is implemented in response to unilateral central injury or asymmetrical sensory deprivation in order to substantially restore symmetry in the control of posturo-locomotor functions. Data are discussed in the context of CNS structure-function relationship.